Strategies of Quran and Hadith Subject Teachers in the Tahfidz Program - Nur Astuty Laba; Kasim Yahiji; Sitti Rahmawati Talango; Moh. Sain (Global Action and Education for Society, 2026)
This study aims to describe the strategies employed by Al-Qur’an Hadis teachers in the tahfidz program at MAN 1 Kabupaten Gorontalo and to identify the obstacles encountered in its implementation. This research employed a qualitative method with a phenomenological approach. Data were collected through observation, in-depth interviews, and documentation involving the head of the madrasah, Al-Qur’an Hadis teachers, program coordinators, and tahfidz students as informants. The data were analyzed through data reduction, data display, and conclusion drawing and verification. Data validity was strengthened through source triangulation, technique triangulation, and member checking. The findings show that the tahfidz program at MAN 1 Kabupaten Gorontalo is implemented regularly and systematically, particularly through additional memorization and murojaah activities. Al-Qur’an Hadis teachers function as mentors, motivators, and facilitators who guide students in increasing memorization, maintaining previous memorization, improving recitation quality, and developing discipline. The main obstacles include limited memorization time, varied student memorization abilities, less supportive home environments, and fluctuating student motivation and consistency in murojaah. This study emphasizes that the success of a tahfidz program is determined not merely by the quantity of memorization, but also by teacher strategies, continuous guidance, institutional support, and students’ commitment to sustained engagement with the Qur’an.